Development of a predictive nomogram for switching immunosuppressive drugs in pediatric liver transplant recipients - Gu, Guangxiang; Zhou, Tao; Zong, Zhipeng; Zhang, Jianjun (Frontiers in Pediatrics, 2023)
Background: Tacrolimus (TAC) is the preferred calcineurin inhibitor (CNI) for pediatric liver transplant recipients. However, some recipients may not achieve the desired therapeutic window concentration of TAC, leading to poor prognosis. This study aimed to develop a clinical model that can predict the effectiveness of TAC in pediatric liver transplant recipients and help clinicians quickly identify cyclosporin as an alternative. Methods: We retrospectively analyzed data from 2032 pediatric liver transplant recipients who underwent surgery at Renji Hospital, Shanghai Jiaotong University School of Medicine between 2006 and 2019. Demographic, comorbidity and pre-operative laboratory data were collected, and a nomogram was constructed using multivariate logistic regression analysis to estimate the risk of poor therapeutic outcomes for TAC-based immunosuppression. Results: The constructed nomogram included seven parameters, namely recipient CYP3A4 genotype, pre-transplant cholangitis, GRWR, spleen long diameter, serum albumin, graft volume reduction, and donor CYP genotype. The nomogram showed good discriminative ability with an area under the receiver operating characteristic curve (AUC) of 74.5% and good calibration. Decision curve analysis indicated a high potential clinical application of the model. Conclusions: This simple clinical model effectively predicts the risk of poor therapeutic outcomes in pediatric liver transplant recipients who receive TAC-based immunosuppression. Clinicians can use the model to identify cyclosporin as an alternative quickly, potentially improving patient prognosis.